Association of blood trace minerals and nocturia in young and middle-aged adults: a cross-sectional study based on NHANES - Su, Quanxin; Zhang, Yanyu; Fan, Weiwei; Tang, Qizhen; Wang, Kenan (Frontiers in Nutrition, 2025)
ObjectiveThe mechanism underlying nocturia in young and middle-aged individuals remains unclear. This study aimed to investigate the association between blood levels of trace minerals and the occurrence of nocturia.MethodsThis cross-sectional study utilized data from the 2021–2023 National Health and Nutrition Examination Survey (NHANES). Linear regression models and subgroup analyses were employed to assess the relationship between blood concentrations of trace minerals including lead, cadmium, total mercury, manganese, and selenium and nocturia. Dose–response relationships were analyzed using smoothed curve fitting.ResultsA total of 2,099 participants were included in the analysis. In unadjusted regression models, blood levels of cadmium and manganese were significantly and positively associated with nocturia in young adults, whereas blood selenium levels were significantly and inversely associated. These associations remained statistically significant after adjusting for relevant covariates in multivariate linear regression analyses. Subgroup analysis revealed that among participants who reported alcohol consumption, those with higher blood cadmium levels had a significantly increased risk of nocturia (OR = 1.626, 95% CI: 1.305–2.026, p < 0.0001). Interaction testing indicated a significant difference in the effect of blood cadmium on nocturia across drinking status. A threshold effect was observed for selenium: when blood selenium levels were below 2.15 μmol/L, the risk of nocturia decreased significantly as selenium levels increased (p < 0.05). No significant associations were found between blood levels of lead or mercury and nocturia in any of the models.ConclusionBlood levels of cadmium, manganese, and selenium are significantly associated with nocturia in young and middle-aged adults. These findings suggest that urologists should consider the potential role of trace mineral levels in the prevention and management of nocturia.